STRUKTUR KOMUNITAS PERIFITON PADA SUBTRAT KACA DILOKAIS PEMELIHARAAN KERANG HIJAU (Perna viridis ) DI PERAIRAN TELUK JAKARTA - Arman, Entang (Jurnal Hidrosfir Indonesia, 2006)
Perifiton are water microorganisms that live sessil on the substrat, and they contribute to build sea water biodiversity. Perifiton are able to live on the substrat that there is no life before so that perifiton can be mentioned as the pioneer to build a new ecosystem. Perifiton community can cause new community such as mussel community and fish community with the result that they form a new ecosystem. This perfiton role is used in green mussel culture in Kamal Muara, Jakarta Bay. This research tries to estimate the perifiton community growth that lives in the area of green mussel culture in Kamal Muara. The research shows that perifiton community is dominated by Bacillariophyceaeand Chlorophyceae. The value of biodiversity index is 1.72-301, the value of evennes index is 0.39-0.72 and the dominancy index is 0.17-0.57.